1984
DOI: 10.1161/01.cir.70.5.824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enzymatic and anatomic estimates of myocardial infarct size in man.

Abstract: Enzymatic estimates of myocardial infarct size based on plasma levels of MB creatine kinase (MB-CK) were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(38 citation statements)
references
References 46 publications
(12 reference statements)
3
34
1
Order By: Relevance
“…Several clinical studies have produced convincing correlations between enzymatic and histologic estimates of infarct size. n - 27 In our study, the correlation between the cumulative cytoplasmic HBDH and cumulative CK release is higher (r=0'96, n=21, P<O·OOOI) compared to the correlation between the cumulative HBDH and cumulative troponin-T release (r=0'84, n=21, P<O·OOOI). Recently, Omura 28 showed a good correlation between the late troponin-T peak and left ventricular ejection fraction (r=0'68), injury extent score (r=0'71) and severity score (r = 0'66).…”
Section: Discussioncontrasting
confidence: 52%
“…Several clinical studies have produced convincing correlations between enzymatic and histologic estimates of infarct size. n - 27 In our study, the correlation between the cumulative cytoplasmic HBDH and cumulative CK release is higher (r=0'96, n=21, P<O·OOOI) compared to the correlation between the cumulative HBDH and cumulative troponin-T release (r=0'84, n=21, P<O·OOOI). Recently, Omura 28 showed a good correlation between the late troponin-T peak and left ventricular ejection fraction (r=0'68), injury extent score (r=0'71) and severity score (r = 0'66).…”
Section: Discussioncontrasting
confidence: 52%
“…The maximum concentration of CK-MB is related to the grade of myocardial damage, [23][24][25][26] and the present study showed a close relationship between the maximum concentrations of M and CK-MB. The study data suggested that the maximum concentration of M, which was obtained at 6-12 h after onset, could be related to the grade of myocardial damage.…”
Section: Relationship Between Maximum Concentrations Of Serum Myoglobsupporting
confidence: 77%
“…The MB heterodimer has been found to comprise between 1% and 22% of the total creatine kinase activity present in human myocardium (3), but is absent from extracts of normal skeletal muscle or brain (4). Accordingly, analysis of plasma MB creatine kinase activity has been used extensively for detection of acute myocardial infarction and quantification of the extent of myocardial injury in patients (5).…”
Section: Introductionmentioning
confidence: 99%
“…Isoelectric points of MB isoforms were determined with the PhastSystem and PhastGel (both Pharmacia Fine Chemicals) containing ampholytes in the pH range of4.0-6.5. Purified isoforms and standards (0.5 Mg) with known pI were prefocused at 2,000 V, 2.0 mA constant power for 5 min, and separated at 2,000 V, 5.0 mA for 20 min at 150C.…”
Section: Introductionmentioning
confidence: 99%